The effects of a script training programme on communication and social skills of a child with autism disorder spectrum - Cabrera Barrios, Andrea; González del Yerro Valdés, Asunción; Igea Durán, Lorena (Revista de Investigación en Logopedia, 2026)
Script training is able to improve the social and linguistic development of children with difficulties. The aim of this study is to analyze the effects that this intervention has on the skills of a five-years-old child with autism disorder spectrum and some of the factors that condition it. The program was applied in two contexts during eight and seven sessions. The child’s peers only participated in the second context. A pre-post design was used to analyze the effects of the program and a concurrent multiple baseline design across behaviors, to verify that the changes observed were due to the intervention program. The dependent variables were linguistic skills: -mean length of utterance (MLU), maximum length of utterance (MxLU) and some grammar structures- and social skills: the duration of the interactions, using another person’s name, play invitations, greetings and courtesy statements. The results showed an improvement in all de dependent variables, that this improvement were greater in the second context of intervention, and that that there were significant correlations between the relevant grammar structures and the teaching episodes. The role played by the adult, the peers and the “experiences scenes” are argued.
Keywords: Script based intervention; autism spectrum disorder; teaching episodes; linguistic and social skills